2009
DOI: 10.1111/j.1365-2966.2009.14414.x
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of star formation quenching with internal galaxy properties and environment

Abstract: We investigate the correlation of star formation quenching with internal galaxy properties and large‐scale environment (halo mass) in empirical data and theoretical models. We make use of the halo‐based group catalogue of Yang and collaborators, which is based on the Sloan Digital Sky Survey. Data from the Galaxy evolution explorer are also used to extract the recent star formation rate. In order to investigate the environmental effects, we examine the properties of ‘central’ and ‘satellite’ galaxies separatel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
225
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 185 publications
(246 citation statements)
references
References 124 publications
17
225
3
1
Order By: Relevance
“…Many studies based on semi-analytic models have shown that bulge-dominated galaxies in massive halos tend to be red and quiescent (Bower et al 2006;Croton et al 2006;Somerville et al 2008;Kimm et al 2009;Lang et al 2014), in general qualitative agreement with our results. As shown by e.g.…”
Section: Comparison With Other Theoretical Studiessupporting
confidence: 92%
“…Many studies based on semi-analytic models have shown that bulge-dominated galaxies in massive halos tend to be red and quiescent (Bower et al 2006;Croton et al 2006;Somerville et al 2008;Kimm et al 2009;Lang et al 2014), in general qualitative agreement with our results. As shown by e.g.…”
Section: Comparison With Other Theoretical Studiessupporting
confidence: 92%
“…Comparing the observations to the results of Kimm et al (2009) (not shown in Fig. 2), our observed, quiescent fractions at galaxy masses below log(M stellar /M⊙) < 10 are somewhat lower than theirs, particularly for satellite galaxies.…”
Section: The Stellar Mass Dependence Of Quiescent Galaxiessupporting
confidence: 72%
“…2), our observed, quiescent fractions at galaxy masses below log(M stellar /M⊙) < 10 are somewhat lower than theirs, particularly for satellite galaxies. Kimm et al (2009) use the Yang catalogue based on the SDSS data similar to our analysis, adopt the same magnitude cut and perform a completeness correction. However, they use SFR estimates based on full SED modelling, while Brinchmann et al (2004) -as used in our analysis -have estimated the SFR via emission lines.…”
Section: The Stellar Mass Dependence Of Quiescent Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimm et al 2009;Kimm, Yi & Khochfar 2011;Wang et al 2014;Hirschmann et al 2014;Phillips et al 2015). While satellites are rapidly quenched -following infall -in the models, analysis of satellite populations identified in the Sloan Digital Sky Survey (SDSS, York et al 2000) instead find that quenching proceeds remarkably slowly, such that a typical e-mail: sfilling@uci.edu † e-mail: cooper@uci.edu ‡ Einstein fellow satellite with M 10 8 M orbits within its host halocontinuing to form stars -for ∼ 3 − 7 Gyr before being quenched (De Lucia et al 2012;Wetzel et al 2013;Wheeler et al 2014).…”
Section: Introductionmentioning
confidence: 99%